Sporadic Creutzfeldt–Jakob disease is associated with reorganization of metabolic connectivity in a pathological brain network. (12th January 2023) - Rus, Tomaž; Mlakar, Jernej; Ležaić, Luka; Vo, An; Nguyen, Nha; Tang, Chris; Fiorini, Michele; Prieto, Elena; Marti‐Andres, Gloria; Arbizu, Javier; Eidelberg, David; Trošt, Maja
Abstract: Background and purpose: Although sporadic Creutzfeldt–Jakob disease (sCJD) is a rare cause of dementia, it is critical to understand its functional networks as the prion protein spread throughout the brain may share similar mechanisms with other more common neurodegenerative disorders. In this study, the metabolic brain network associated with sCJD was investigated and its internal network organization was explored. Methods: We explored 2‐[ 18 F]fluoro‐2‐deoxy‐d ‐glucose positron emission tomography (FDG‐PET) brain scans of 29 sCJD patients, 56 normal controls (NCs) and 46 other dementia patients from two independent centers. sCJD‐related pattern (CJDRP) was identified in a cohort of 16 pathologically proven sCJD patients and 16 age‐matched NCs using scaled subprofile modeling/principal component analysis and was prospectively validated in an independent cohort of 13 sCJD patients and 20 NCs. The pattern's specificity was tested on other dementia patients and its clinical relevance by clinical correlations. The pattern's internal organization was further studied using graph theory methods. Results: The CJDRP was characterized by relative hypometabolism in the bilateral caudate, thalami, middle and superior frontal gyri, parietal lobe and posterior cingulum in association with relative hypermetabolism in the hippocampi, parahippocampal gyri and cerebellum. The pattern's expression significantly discriminated sCJD from NCs and other dementia patients ( p < 0.005; receiver operating characteristic analysis CJD vs. NCs area under the curve [AUC] 0.90–0.96, sCJD vs. Alzheimer's disease AUC 0.78, sCJD vs. behavioral variant of frontotemporal dementia AUC 0.84). The pattern's expression significantly correlated with cognitive, functional decline and disease duration. The metabolic connectivity analysis revealed inefficient information transfer with specific network reorganization. Conclusions: The CJDRP is a robust metabolic biomarker of sCJD. Due to its excellent clinical correlations it has the potential to monitor disease in emerging disease‐modifying trials.